Leadership in English language teaching and learning (University of Michigan Press, 2008)
Leadership skills are indispensable in language teaching and learning, and the effectiveness of these skills directly affect the quality of language education, the soundness of a program, and the satisfaction level of both teachers and students in the language classrooms and beyond. nbsp; Part 1 of this collection provides the theoretical underpinnings of leadership development.nbsp; Part 2 focuses on leadership skills and strategies on the topics of interpersonal communication, personal organization skills, and program organization skills.nbsp; Part 3 discusses ELT leadership issues in U.S. public schools.